Answer:
Part a)
[tex]W = -\frac{Gm_1m_2}{b} + \frac{Gm_1m_2}{a}[/tex]
Part b)
[tex]W = 1.3 \times 10^{11} J[/tex]
Explanation:
Part a)
Here we know that force of gravitation is given as
[tex]F = \frac{Gm_1m_2}{r^2}[/tex]
now we have to find work done to move the mass from initial to final position
[tex]W = \int F.dr[/tex]
[tex]W = \int (\frac{Gm_1m_2}{r^2}).dr[/tex]
now we have
[tex]W = - \frac{Gm_1m_2}{r}[/tex]
since we move the object from r = a to r = b so we will have
[tex]W = -\frac{Gm_1m_2}{b} + \frac{Gm_1m_2}{a}[/tex]
Part b)
As per above equation we know that the work done is given as
[tex]W = -\frac{Gm_1m_2}{b} + \frac{Gm_1m_2}{a}[/tex]
here we can say that
[tex]m_1 = 2500 kg[/tex]
[tex]m_2 = 5.98 \times 10^{24} kg[/tex]
[tex]a = 6.37 \times 10^6 m[/tex]
[tex]b = (6.37 \times 10^6 + 3.5 \times 10^7) m[/tex]
now plug in all values in above equation
[tex]W = (6.67 \times 10^{-11})(5.98 \times 10^{24})(2500)(\frac{1}{6.37\times 10^6} - \frac{1}{(6.37 \times 10^6 + 3.5 \times 10^7)})[/tex]
[tex]W = 1.3 \times 10^{11} J[/tex]